2015
DOI: 10.1179/2045772315y.0000000032
|View full text |Cite
|
Sign up to set email alerts
|

Deep venous thrombosis in patients with chronic spinal cord injury

Abstract: Context/Objective: Deep venous thrombosis (DVT) is a well-known complication of an acute spinal cord injury (SCI). However, the prevalence of DVT in patients with chronic SCI has only been reported in a limited number of studies. The aim of our study was to examine the prevalence of DVT in patients with SCI beyond three months after injury. Design: Cross-sectional study. Setting: Rehabilitation Department at the Bydgoszcz University Hospital in Poland. Participants: Sixty-three patients with SCI that were more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 26 publications
3
37
0
Order By: Relevance
“…DVT was diagnosed in McKinley et al [18] clinically or with 1–125 labelled fibrinogen uptake citation, impedance plethysmography, Doppler or venography. In Mackiewicz-Mile et al [22] DVT was diagnosed by D-dimer and ultrasound Doppler. Lamb et al [23] accepted any diagnostic method for VTE for inclusion; however we could not tell how patients were diagnosed with PE or DVT from the report.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DVT was diagnosed in McKinley et al [18] clinically or with 1–125 labelled fibrinogen uptake citation, impedance plethysmography, Doppler or venography. In Mackiewicz-Mile et al [22] DVT was diagnosed by D-dimer and ultrasound Doppler. Lamb et al [23] accepted any diagnostic method for VTE for inclusion; however we could not tell how patients were diagnosed with PE or DVT from the report.…”
Section: Resultsmentioning
confidence: 99%
“…We could not tell the sub-acute DVT incidence separately from the reported findings. In the third study, Mackiewicz-Milewska et al [22] presented an abstract of a prospective case series that included 63 spinal patients from the rehabilitation department in Bydgoszcz, Poland. The study reported five DVTs in the sub-acute phase diagnosed with Doppler ultrasound.…”
Section: Resultsmentioning
confidence: 99%
“…Although much has been debated about the incidence of DVT in acute SCI patients, the problem of DVT in subacute and chronic SCI is rarely discussed. 6 The guidelines as per the consortium for spinal cord medicine and ACCP suggest the use of chemical and mechanical prophylaxis for prevention of DVT in acute spinal cord injury patients. 7,8 But in cases of subacute and chronic spinal cord injury who are undergoing rehabilitation or admitted for various medical ailments, the chemical prophylaxis for DVT is difficult to supervise.…”
Section: Discussionmentioning
confidence: 99%
“…For a study with 95% confidence level, with prevalence of DVT considered as 7.9% 6 and 7% absolute error, the sample size calculated was 60.…”
Section: Methodsmentioning
confidence: 99%
“…18,19 Three observational studies examined the role of D-dimer as a screening marker for VTE in patients with SCI. [20][21][22] Two studies reported no difference in D-dimer values in SCI patients who developed VTE compared with those without any events in acute 20 or chronic 21 phases after injury. Another study reported that D-dimer can be utilized as a surrogate marker to predict the likelihood of developing DVT in patients with cervical SCI, and concluded that the optimal timing of performing a D-dimer test should be 2 weeks after injury.…”
Section: Risk Factors For Venous Thromboembolismmentioning
confidence: 99%